1987
DOI: 10.1073/pnas.84.19.6909
|View full text |Cite
|
Sign up to set email alerts
|

Structural and pathological effects of synthesis of hepatitis B virus large envelope polypeptide in transgenic mice.

Abstract: Overproduction of the hepatitis B virus (HBV) large envelope polypeptide by transgenic mice containing the entire HBV envelope coding region leads to the formation of extremely long (up to 800 nm), occasionally branching, filamen-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
269
1
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(286 citation statements)
references
References 14 publications
(14 reference statements)
14
269
1
2
Order By: Relevance
“…14,15 The pathogenetic association of viral load and cell death has been documented in HepG2 lines and transgenic mice models. 16,17 Recently, the detection of the precore mutant 5,6,9,18 and mutational changes in the S and pre-S genome 19,20 in a few patients raised the possibility of the pathogenetic significance of viral mutations.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The pathogenetic association of viral load and cell death has been documented in HepG2 lines and transgenic mice models. 16,17 Recently, the detection of the precore mutant 5,6,9,18 and mutational changes in the S and pre-S genome 19,20 in a few patients raised the possibility of the pathogenetic significance of viral mutations.…”
Section: Discussionmentioning
confidence: 99%
“…46 Different from the findings with MHBs DNA, co-immunizations of LHBs encoding DNA with either pcD/3-IL2 or pRJB-GM had no augmenting effect on cellular and humoral immune responses to HBV envelope proteins. LHBs cannot be secreted by itself in hepatoma and other cell lines, including myoblast cells, even though it is targeted co-translationally to the rough endoplasmic reticulum 34,47,48 and inhibits the secretion of MHBs and SHBs by forming heteromultimers when produced in large amounts. A recent study demonstrated that LHBs itself can form 20-nm particles which are retained in a post-rough endoplasmic reticulum compartment, possibly by interacting with calnexin and other regulatory endoplasmic reticulum proteins.…”
Section: Discussionmentioning
confidence: 99%
“…21 Electron microscopy studies of liver sections performed from the mice overexpressing the L protein showed subviral envelope filaments of approximately 20 nm in diameter and very extensive length (up to 800 nm) that accumulate in the ER. 20 The L-protein retention has been also associated with a peculiar syndrome called fibrosing cholestatic hepatitis (FCH), characterized by marked hepatocellular ballooning and prominent cholestasis but minimal inflammation, that occurs in immunosuppressed HBV carriers. 22,23 The same accumulation of HBV subviral envelope filaments in intracellular compartments has been observed by electron microscopy in liver samples of patients suffering from FCH.…”
Section: Discussionmentioning
confidence: 99%
“…This intracellular accumulation is seen in patients in late phases of chronic HBV infection, especially at the phase of cirrhosis, when a high level of intracellular expression of HBV surface proteins is associated with a low level of serum HBV surface proteins. 18,19 Hepatocytes of transgenic mice bearing such L-protein retention accumulation develop characteristic cytopathic effects 20 that can induce a liver regeneration leading to the development of a liver cancer in this model. 21 Electron microscopy studies of liver sections performed from the mice overexpressing the L protein showed subviral envelope filaments of approximately 20 nm in diameter and very extensive length (up to 800 nm) that accumulate in the ER.…”
Section: Discussionmentioning
confidence: 99%